Analysis of the current status and characteristics of osteoporosis in adult hemophilia patients based on high-resolution peripheral quantitative computed tomography: a case control study - Ying Liu; Ying Ge; Mingnan Shi; Li Zhang; Lixia Chen; Weibo Xia (BMC Musculoskeletal Disorders)
Abstract Background Current research on osteoporosis (OP) in hemophilia is insufficient. The suitability of high-resolution peripheral quantitative computed tomography (HR-pQCT) for evaluating osteoporosis in hemophilia remains unclear. Aim To investigate the current status of osteoporosis and the applicability of HR-pQCT in adult hemophilia patients. Methods Thirty three hemophilia patients aged 23–49 years were recruited. X-ray examinations were performed on the bleeding joints. Dual energy X-ray absorptiometry (DXA) and HR-pQCT were used to assess bone mineral density (BMD). The HR-pQCT values of the distal tibia and radius were compared between hemophilia patients and healthy controls(HCs). Results All bleeding joints showed local osteoporosis on X-ray. Only 33.3% of patients had a hip BMD lower than the expected value according to DXA. The Tb.vBMD(98.5 ± 44.2 mg/cm3), Tt.Ar(612.5 ± 163.5mm2),Tb.Ar(487.0 ± 175.6mm2), Ct.Ar(117.0 ± 25.7mm2), Tb.BV/TV(0.2 ± 0.1), Tb.N(0.9 ± 0.3 1/mm), Ct.Pm(96.3 ± 13.8 mm) of the distal tibia and Tt.Ar(248.4 ± 53.1mm2),Tb.Ar(186.0 ± 55.1mm2), Ct.Ar(66.1 ± 14.4 mm2), Ct.Pm(68.1 ± 7.1 mm) of the distal radius in the hemophilia group was significantly lower than the HCs(tibia Tb.vBMD:186.4 ± 44.3mg/cm3, Tt.Ar:906.8 ± 135.0mm2,Tb.Ar:743.7 ± 137.6mm2, Ct.Ar:169.3 ± 21.9mm2,Tb.BV/TV:0.3 ± 0.1, Tb.N:1.5 ± 0.2 1/mm,Ct.Pm:117.8 ± 8.2 mm; radius Tt.Ar:285.7 ± 35.6 mm2, Tb.Ar:83.8 ± 7.9mm2, Ct.Ar:0.3 ± 0.1mm2, Ct.Pm:80.2 ± 4.3 mm) with statistically significant differences (p < 0.05). Correlation analysis showed a positive correlation (r = 0.768, p = 0.016) between femoral neck BMD with DXA and total volumetric BMD(Tt.vBMD) at the distal tibia. Conclusion The bone health status of adult hemophilia patients in China is worrying. The occurrence of OP may be accompanied by varying degrees of bone loss, bone destruction, and structural abnormalities observed in both trabecular and cortical bones of the upper and lower limbs. The condition of the trabecular bones in the lower limbs is particularly severe. The correlation between BMD measurements obtained from HR-pQCT and DXA is strong.